Energy-Saving Lighting Lamps and Their Parameters (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article provides information on the structure, working principles, history of creation, and economic indicators of energy-saving lighting devices-LED lamps. Energy transitions in LED lamps, recombination processes, energy brightness of sources and the parameters of these lamps were analyzed in comparison with the parameters of incandescent lamps.